Reductive removal of As(V) and As(III) from aqueous solution by the UV/sulfite process: Recovery of elemental arsenic. (1st September 2022) - Wang, Jianbing; Liu, Jiyong; Peng, Xianjia; He, Mengchang; Hu, Xingyun; Zhao, Jinmin; Zhu, Feng; Yang, Xin; Kong, Linghao
Highlights: Above 99.9 % of arsenic was reductively removed by the UV/sulfite process. Valuable elemental arsenic (As(0)) with high purity (> 99.5 wt%) was recovered. Hydrated electrons (eaq − ) and H radicals are responsible for arsenic reduction. SO3 − radicals suppress the removal of arsenic by oxidizing As(0) and As(III). Arsenic removal is effective in complex water matrices with low energy consumption. Abstract: The removal of arsenic (As(V) and As(III)) from contaminated water has attracted great attention. However, the generation of arsenic-containing hazardous waste by traditional methods has become an inevitable environmental problem. Herein, a UV/sulfite advanced reduction method was proposed to remove As(V) and As(III) from aqueous solution in the form of valuable elemental arsenic (As(0)), thus avoiding the generation of arsenic-containing hazardous waste. The results showed that greater than 99.9% of As(V) and As(III) were reduced to the high purity As(0) (> 99.5 wt%) with the residual arsenic concentration below 10 μg L −1 . The hydrated electrons (eaq − ), H and SO3 − radicals are generated by the UV/sulfite process, of which eaq − and H serve as reductants of As(V) and As(III) while the SO3 − radicals inhibit arsenic reduction by oxidizing arsenic. The effective quantum efficiency (Φ) for the formation of As(0) in the As(V) and As(III) removal process is approximately 0.0078 and 0.0055 mol/Einstein, respectively. The reduction of arsenic is favorable under alkaline conditions (pH > 9.0) due to the higher photolysis efficiency of SO3 2− than HSO3 − (pKa  = 7.2) and higher stability of eaq − /H under alkaline conditions. The presence of dissolved oxygen (O2 ), NO2 −, NO3 −, CO3 2−, PO4 3− and humic acid (HA) inhibited arsenic reduction through light blocking or eaq − /H scavenging effects while Cl −, SO4 2−, Ca 2+ and Mg 2+ had negligible effects on arsenic reduction. The proposed method can effectively remove and recover arsenic from contaminated water at a low cost, demonstrating feasibility for practical application. This study provides a novel technology for the reductive removal and recovery of arsenic from contaminated water. Graphical abstract: Image, graphical abstract